2021
DOI: 10.21203/rs.3.rs-1080624/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular analyses in wheat and Aegilops tauschii reveals a new orthologue of the leaf rust resistance gene Lr19 on 7DL chromosome of Ae. tauschii

Abstract: Leaf rust is one of the most devastating wheat diseases worldwide, to which many resistance genes have been ‎successfully introgressed ‎from wheat wild relatives. Though the Thinopyrum ‎ponticum-derived leaf rust resistance gene Lr19, is widely effective worldwide and previous studies ‎have shown its likely presence in Aegilops tauschii, no ‎thorough investigation has been conducted to confirm this. The present study aimed to ‎examine the presence of Lr19 in Ae. tauschii using a collection of molecular and bio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Among them, Lr9 , Lr19 , Lr24 , Lr34 , Lr37 , Lr38 , Lr46 , Lr47 , Lr51 , Lr53 , Lr68 and Lr42 are known to confer effective resistance to leaf rust according to the field survey in Sichuan province, China ( Gao et al, 2019 ). Lr19 was derived from the grass Agropyron elongatum and was transferred to the long arm of wheat chromosome 7D ( Pourkhorshid et al, 2022 ). Although resistance of Lr19 has been overcome by some virulent Pt races in Mexico ( Huerta and Singh, 1994 ), Russia ( Lind and Gultyaeva, 2007 ), Ukraine ( Elyasi-Gomari and Panteleev, 2006 ) and India ( Bhardwaj et al, 2005 ), it still showed high resistance to all the collected Pt races in China ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Lr9 , Lr19 , Lr24 , Lr34 , Lr37 , Lr38 , Lr46 , Lr47 , Lr51 , Lr53 , Lr68 and Lr42 are known to confer effective resistance to leaf rust according to the field survey in Sichuan province, China ( Gao et al, 2019 ). Lr19 was derived from the grass Agropyron elongatum and was transferred to the long arm of wheat chromosome 7D ( Pourkhorshid et al, 2022 ). Although resistance of Lr19 has been overcome by some virulent Pt races in Mexico ( Huerta and Singh, 1994 ), Russia ( Lind and Gultyaeva, 2007 ), Ukraine ( Elyasi-Gomari and Panteleev, 2006 ) and India ( Bhardwaj et al, 2005 ), it still showed high resistance to all the collected Pt races in China ( Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%